International secondary science grade 7 workbook - Fullick, Ann; Hulme, Philippa Gardom; Jones, Catherine (Karachi: Oxford university press, 2024)
Comprehensive match to Pakistan National Curriculum 2022 framework. Rigorous challenge materials that build a strong foundation for future learning. Extensive preparation for the exams to build confidence and support performance, lots of crossover materials for seamless transition to higher levels.
Keywords: Oxford science - textbook